A comprehensive review on the medicinal usage of Podocarpus species: Phytochemistry and pharmacology. (28th June 2023) - Deng, Zhou; Sheng, Feiya; Yang, Si-Yu; Liu, Yi; Zou, Liang; Zhang, Le-Le
Abstract: Ethnopharmacological relevance: Plants of the Podocarpus species belong to the Podocarpaceae family and are largely distributed in the southern hemisphere. Beside the commercially and ecologically valuable, plants of the Podocarpus species are also used in traditional medicines in some countries for treating asthma, fever, venereal diseases, eye diseases, etc . Aim of the study: In recent decades, the identities and pharmacological activities of phytochemicals extracted from Podocarpus plants have been widely studied. However, there have been no comprehensive and systematic reviews. This article aims to systematically review the latest research on the putative mechanisms underlying pharmacological actions of phytochemicals from the Podocarpus species, as well as to lay a foundation for promoting the development of plant resources from this genus, further drug research, and product development. Materials and methods: A comprehensive search of PubMed, Google Scholar, Web of Science, Elsevier and CNKI databases was conducted using the keywords " Podocarpus ", "traditional usage", "phytochemistry", "pharmacology", "nagilactone", etc . Related papers published among July 1964 to February 2023 were collected to summarize the research progress. All plant names were determined through the "The Plant List" (http://www.theplantlist.org/ ). Results: To date, 262 chemical constituents have been isolated and identified from 26 Podocarpus plants; among these, norditerpene bilactone is the main pharmacologically active component. Norditerpene bilactones are reported to have anti-cancer, anti-inflammatory, antioxidant, antibacterial, anti-tyrosinase, neuroprotective, anti-plasmodial, anti-mutagenic, and anti-atherosclerotic properties as well as other pharmacological activities, which support its traditional uses. Conclusion: Extensive studies on phytochemistry and pharmacology of Podocarpus species lead to discovery of a series of hopeful leading compounds with unique chemical structure, especially the nor- and bis-norditerpenoid dilactones with four isoprene units. These compounds have been proved to possess various pharmacological activities. This review will provide a reference for further research and promote the idea of combining modern research with traditional medicinal applications of Podocarpus plants. Graphical abstract: Image 1